-6u+20=4(u-5)

Simple and best practice solution for -6u+20=4(u-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6u+20=4(u-5) equation:



-6u+20=4(u-5)
We move all terms to the left:
-6u+20-(4(u-5))=0
We calculate terms in parentheses: -(4(u-5)), so:
4(u-5)
We multiply parentheses
4u-20
Back to the equation:
-(4u-20)
We get rid of parentheses
-6u-4u+20+20=0
We add all the numbers together, and all the variables
-10u+40=0
We move all terms containing u to the left, all other terms to the right
-10u=-40
u=-40/-10
u=+4

See similar equations:

| x/7-10=-18 | | 1.5^x-1=14.5 | | 7(u+5)=9u+17 | | -5(w+2)=-7w+8 | | 32x/435=179 | | Y=x2-6x+5 | | 1.5^x=14.5 | | 9(w-^)=-8w-20 | | F(x)=0.1x^2+10x+450 | | 3y+17=-8(y-9) | | Y=x2-2x-8 | | 12(x-5)=-24 | | 5^3+x-4•7x=43 | | 4(2)-8y=5 | | 65+x=90 | | -6(y-3)=6y-30 | | -15+4(2-5y)=-7(y-4)+4 | | 3x+4x=68 | | 27=-9t-9 | | _6(y-)3=6y-30 | | -50=10z-15z | | 39+x=90 | | 4x+32=6(x+3) | | 3x-18=30+9x | | 4x-9=100 | | 16-y=13 | | 34+x=90 | | 2.5x+9=29 | | 12y-30=0 | | 7(c-17)=-28 | | 10x=6x+45 | | -4(-4x-7)=108 |

Equations solver categories